The mitigation hierarchy upside down – a study of nature protection measures in Danish infrastructure projects. Issue 4 (4th July 2018) - Larsen, Sanne Vammen; Kørnøv, Lone; Christensen, Per
Abstract: This paper presents a Danish study of mitigation directed at nature protection in environmental impact assessment (EIA) of infrastructure projects. The study is based on a document analysis of EIA reports, a workshop held with EIA professionals, and a study of two cases. The paper takes a point of departure in the mitigation hierarchy as a central conceptual framework, identifies which mitigation measures have been suggested in the EIA reports, and compares this to the mitigation hierarchy. Further, the paper explores the dynamics behind which mitigation measures are chosen and later implemented. The findings point to a discrepancy between the prevention principle embedded in the mitigation hierarchy and the actual EIA practice with increased use of nature compensation. Further, the research reveals significant variation in the design of mitigation measures, e.g. in the level of detail used in describing them and the level of clarity as to aims and actions.